Quantification urban heat island (UHI) using the local climate zone classification (LCZ): A case study in Constantine - Dounia KHELLAF; Saliha ABDOU (Revue Nature et Technologie, 2022)
The number of issues assigned to the risks of urban warming has highlighted the extremely problematic nature of this phenomenon that affects the local climate characteristics of urban areas. In this context, city planners are strongly solicited to consider climatic information in their process of design. The use of classification schemes, such as Local Climate Zone (LCZ) is adapted for this type of application. This contribution aims, through the use of the newly developed climate scheme -called LCZ -, to give a better understanding and more objective assessment of the atmospheric Urban Heat Island (UHI) phenomenon in Constantine (Algeria). The three-step procedure of LCZ workflow has been followed in the case study area, to classify the landscape into fragments that are homogeneous in terms of urban characteristics and thermal features. Urban form parameters have been calculated so as to build LCZ types in the study Area. Two measurement campaigns were carried out using fixed stations; to investigate screen-height air temperature distribution inside two LCZ (LCZ5 ‘’open mid-rise’’, LCZ2 ‘’compact mid-rise). Results showed that air temperature intensity has mainly demonstrated a small daily gap and higher night-time amplitude in urbanized LCZ types.